Sejarah dan Perkembangan Pondok Pesantren di Indonesia - Marhamah, Aulia; Khairani, Ismi; Aini, Nur; Alfayed, Muhammad; Dalimunthe, Putri Ani (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
This research aims to examine the history and development of Islamic boarding schools as Islamic education for a long time in Indonesia. One of the first and oldest Islamic educational institutions in Indonesia is the Islamic boarding school. Islamic boarding school is Islamic religious education which not only teaches about reading the Koran and other books, but also how to teach how to live in Islam. Islamic boarding schools are a place to gain religious knowledge, as well as a place to forge human values and norms to become commendable morals. The influences of Islamic boarding schools on education in Indonesia, namely: the presence of Islamic boarding schools has provided many benefits for the Indonesian nation. People who study Islam are usually called santri. Apart from gaining religious knowledge, the students are also equipped with general knowledge that is ready to welcome changing times. The research method used is qualitative and literature study to evaluate the history and development of Islamic boarding schools in Indonesia. The results showed that pesantren have experienced developments, both in terms of curriculum, educational structure, and the use of technology, but still maintain traditional values that prioritize religious and moral education. Along with the times, pesantren also began to combine general and religious education to produce graduates who not only have strong religious knowledge, but are also ready to face the challenges of the times. Keywords : Education; History; Islam; Islamic Boarding School